3D Printing: 3D Printing of Microgel‐Loaded Modular Microcages as Instructive Scaffolds for Tissue Engineering (Adv. Mater. 36/2020). Issue 36 (8th September 2020) - Subbiah, Ramesh; Hipfinger, Christina; Tahayeri, Anthony; Athirasala, Avathamsa; Horsophonphong, Sivaporn; Thrivikraman, Greeshma; França, Cristiane Miranda; Cunha, Diana Araujo; Mansoorifar, Amin; Zahariev, Albena; Jones, James M.; Coelho, Paulo G.; et al.
Abstract : In article number 2001736, Luiz E. Bertassoni and co‐workers present the use of lithography‐based 3D printing to fabricate a novel modular microcage scaffold system. These hollow microcages can be stacked in thousands of geometric configurations with the ability to scale in size and shape to fit complex tissue defects. Different growth factors and cells can be placed inside each block, enabling cell‐instructive and accelerated repair of musculoskeletal tissue injuries.